The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.2478/johh-2018-0036
|View full text |Cite
|
Sign up to set email alerts
|

Impact of soil compaction on water content in sandy loam soil under sunflower

Abstract: Soil compaction causes important physical modifications at the subsurface soil, especially from 10 to 30 cm depths. Compaction leads to a decrease in infiltration rates, in saturated hydraulic conductivity, and in porosity, as well as causes an increase in soil bulk density. However, compaction is considered to be a frequent negative consequence of applied agricultural management practices in Slovakia. Detailed determination of soil compaction and the investigation of a compaction impact on water content, wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 24 publications
1
8
0
1
Order By: Relevance
“…The presence of salts in the soil pore water reduces the osmotic potential of the solution and the equilibrium water vapor pressure (Nassar and Horton, 1997). Consequently, evaporation rates from a saline soil are expected to be lower compared to solute-free conditions.…”
Section: Evaporation and Soil Salinizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of salts in the soil pore water reduces the osmotic potential of the solution and the equilibrium water vapor pressure (Nassar and Horton, 1997). Consequently, evaporation rates from a saline soil are expected to be lower compared to solute-free conditions.…”
Section: Evaporation and Soil Salinizationmentioning
confidence: 99%
“…Studies on the effect of soil compaction on evaporation, in general, and its relation to salt precipitation, in particular, are scarce. Nassar and Horton (1999) examined salinity and compaction effects on soil water evaporation from bare soils, focusing on water and solute distributions in the soil. They showed that compaction increases cumulative evaporation, due to increased matric suction of the compacted soil, resulting in the increase of the soil water-holding capacity and unsaturated hydraulic conductivity.…”
Section: Evaporation and Soil Compactionmentioning
confidence: 99%
“…A pontosabb növényvédelem és tápanyagutánpótlás lehetővé teszi a vegyszerek hatékonyabb felhasználását, csökkentve a környezeti terhelést és a költségeket. Az automatizált rendszerek és robotok segítségével csökkenthető a kézi munkaerőigény, így a gazdálkodók hatékonyabban tudnak dolgozni [1] [2] [3].…”
Section: Bevezetésunclassified
“…Crop yield is depending on various factors, such as soil type, seed, amount of fertilizer, climatic and local meteorological conditions. Within-field soil differences also influence yield, for instance plough pan (Nagy et al, 2018), soil compaction (Neményi et al, 2008) or soil moisture distribution (Milics et al, 2017;Nagy et al, 2008) plays important role on yield variability. Agricultural activity plays an important role on soil health.…”
Section: Introductionmentioning
confidence: 99%